Static analysis of stitched sandwich beams with functionally graded foam core - Almula, Thamir A. D. M. S. (2013)
In this paper static analysis of a cantilever functionally graded sandwich beam under uniform distributed loads is carried out numerically. The beam is composed of two glass fiber reinforced plastic (GFRP) facesheets and a graded Corecell A-series foam core. The composite skins and foam core are stitched together using the same glass fiber. A finite element (FE) model is developed employing a FE commercial code to determine the stresses and deflections. To find the effect of quality of foam gradation through the thickness of the core on the deflections and stresses numerical experiments are performed. Results revealed that the quality of gradation of the foam core affected the displacements and stresses significantly so that an optimal gradation of foam can minimize the deflection, stresses and weight of the sandwich beam.